Fingolimod Inhibits Inflammation but Exacerbates Brain Edema in the Acute Phases of Cerebral Ischemia in Diabetic Mice - Li, Wanlu; He, Tingting; Jiang, Lu; Shi, Rubing; Song, Yaying; Mamtilahun, Muyassar; Ma, Yuanyuan; Zhang, Zhijun; Tang, Yaohui; Yang, Guo-Yuan; Wang, Yongting (Frontiers in Neuroscience, 2020)
Background and Purpose: Diabetes mellitus increases stroke incidence and mortality and hampers functional recovery after stroke. Fingolimod has been shown to improve neurofunctional recovery and reduce brain infarction after ischemic injury in mice without comorbidities. In this work, we investigated the effects of fingolimod in diabetic mice after transient middle cerebral artery occlusion (tMCAO). Methods: Hyperglycemia was induced by a single bolus streptozotocin injection. Adult male ICR mice (n=86) underwent 1-hour tMCAO surgery and received intraperitoneal injection of fingolimod (1mg/kg) or vehicle immediately after reperfusion. Neurological score, brain infarction, edema, blood brain barrier integrity, apoptosis and inflammation were evaluated at 24 hours after tMCAO. Results: Fingolimod reduced inflammation shown by the reduced number of infiltrated inflammatory cells and lowered Tnfα. It also reduced apoptosis and the ratio of Bcl-2/Bax. However, fingolimod significantly aggravated brain edema and reduced the levels of tight junction proteins ZO-1 and Occludin. The negative impacts of fingolimod on BBB integrity outweighed its beneficial effects in anti-inflammation and anti-apoptosis, which resulted in the lack of improvement in end point outcomes at 24 hours after tMCAO. Conclusion: Caution should be taken in considering the acute treatment using fingolimod for ischemic stroke with diabetes comorbidity.